اتفاق التحكيم في القانون الاتحادي الإماراتي: الإطار المفاهيمي، شروط الصحة، والآثار القانونية - Youssef Hassan Mohammed Alhousani; Baidar Mohammed Mohammed Hasan (Faculty of Syariah and Law, USIM, 2026)
This article examines the arbitration agreement as the cornerstone of the arbitration system under UAE Federal Arbitration Law No. 6 of 2018. It analyses the conceptual framework and legal nature of the arbitration agreement, its formal and substantive validity requirements, as well as the legal effects arising therefrom and the limits of judicial intervention. The study adopts an analytical legal approach based on the interpretation of statutory provisions, supported by doctrinal analysis and relevant judicial trends in the UAE, viewed in light of comparative arbitration standards. The article argues that the UAE legislator has adopted a balanced regulatory approach that strengthens party autonomy while subjecting the arbitration agreement to limited judicial control aimed at safeguarding public policy and fundamental procedural guarantees. It further demonstrates that the effectiveness of arbitration depends not only on the legislative framework, but also on the precision and clarity of drafting arbitration agreements, particularly with regard to their scope, in order to minimise procedural disputes and enhance confidence in arbitration as an effective dispute resolution mechanism.